The role of methylene blue in laparoscopic sleeve gastrectomy - Osama A Abdul Raheem; Mohamed Yousef; Abd-; Hassan A Abdallah; Asmaa Gaber (Wolters Kluwer Medknow Publications, 2016)
Introduction Methylene blue (MB) is a molecule that has been playing important roles in microbiology and pharmacology for some time. It has been widely used to stain living organisms and to treat methemoglobinemia, and lately it has been considered as a drug for photodynamic therapy. Nowadays, it is used in the treatments of basal cell carcinoma, Kaposi's sarcoma, melanoma, and virus and fungal infections. MB has low toxicity and no adverse effects. Patients and methods This study was conducted in Aswan University on female and male patients. Our study was done on 70 patients, who had an average age of 29.8 years, with minimum of 25 years and maximum of 35 years. Patients were studied preoperatively with complete investigations, a multidisciplinary workup including specialist counseling (internal medicine, psychiatry, and anesthesiology), and complete performance status evaluation. Patients were well informed about the surgical procedure, with all potential advantages and possible complications and adverse effects. Then they were proceeded to laparoscopic sleeve gastrectomy and the uses of intraoperative MB to confirm any leaks from the stapler line. Postoperative data regarding fever, tachycardia, vomiting, abdominal pain and distention, abdominal ultrasound for any collection, and complete blood count were recorded. All the above data were collected and analyzed to obtain statistically relevant results. Results Apart from mild abdominal pain and tenderness, and low-grade fever, no collection appeared clinically or by ultrasound examination in all cases. All patients received oral fluids on the third postoperative day, and no vomiting developed. White blood cell count was done for all patients, and they were normal except five patients who developed chest infection with low-grade fever which improved with antibiotic. Before discharging the patients, abdominal ultrasound was done for all, and no collection of fluid appeared. Conclusion Intraoperative MB usage is a safe and effective technique in detecting gastric leak during laparoscopic sleeve gastrectomy.